Hedgehog pathway and smoothened inhibitors in cancer therapies. Issue 5 (June 2018) - Chahal, Kirti K.; Parle, Milind; Abagyan, Ruben
Abstract : The hedgehog (Hh) pathway plays an important role in cancer development and maintenance, as ~25% of all cancers have aberrant Hh pathway activation. Targeted therapy for inhibition of the Hh pathway was thought to be promising for achieving clinical response in the Hh-dependent cancers. However, the results of new clinical trials with smoothened (SMO) antagonists do not show much success in cancers other than basal cell carcinoma. The studies suggest that the Hh pathway involves multiple mechanisms of activation or inhibition in primary cilia and interactions between several related pathways in different types of cells, which makes this pathway extremely complex. The SMO-specific antagonists may not stop all relevant pathways that may lead to escape or development of resistance. Therefore, in the Hh-dependent cancers, the inhibition of two or more oncogenic pathways (including the Hh pathway) with use of a single agent of a suitable multitarget profile or a combination of drugs seems promising for achieving clinical response in patients and decrease in resistance development with prolonged use of the specific SMO antagonists. Furthermore, for studying the effect of new treatments, the inclusion criteria should be more specific for selection of patients with aberrant Hh pathway activity confirmed by tests. These considerations will be very helpful for choosing the right patients and the right drugs for the best therapeutic outcome. Abstract : Supplemental Digital Content is available in the text.